Strengthening health services to deliver nutrition education to promote complementary feeding and healthy growth of infants and young children: formative research for a successful intervention in peri‐urban Trujillo, Peru. Issue 2 (2nd March 2016) - Robert, Rebecca C.; Creed‐Kanashiro, Hilary M.; Villasante, Ruben; Narro, M. Rocio; Penny, Mary E.
Abstract: Formative research is critical for developing effective nutrition‐specific interventions to improve infant and young child (IYC) feeding practices and promote healthy growth. Health workers interact with caregivers during health facility visits, yet there is limited research about how to optimize delivery of such interventions during these visits. The extensive reach of IYC health services globally calls for research to address this gap. In Trujillo, Peru, formative research was conducted to explore complementary feeding practices with caregivers as well as health worker routines and interactions with caregivers related to feeding and healthy growth; results informed the development and delivery of an educational intervention. Multiple qualitative methods were used to collect data on a purposive sample of health workers and caregivers from three health facilities and communities: household trials followed. Complementary feeding messages with doable behaviours were developed, and three were selected as key to promote based on their nutritional impact and cultural acceptability. In the health facilities, medical consultation, well‐child visits and nutrition consultation all dealt with aspects of IYC nutrition/growth during their interactions with caregivers but were independent and inconsistent in approach. A nutrition education strategy was developed based on consistency, quality and coverage in the IYC health services. We conclude that formative research undertaken in the community and IYC health services was critical to developing a successful and culturally relevant intervention to promote optimal complementary feeding practices and healthy growth during interactions between health workers and caregivers at routine health facility visits. © 2016 John Wiley & Sons Ltd